The Role of Depletion of Gut Microbiota in Osteoporosis and Osteoarthritis: A Narrative Review - Guan, Zhiyuan; Luo, Liying; Liu, Shengfu; Guan, Zhiqiang; Zhang, Qinggang; Li, Xu; Tao, Kun (Frontiers in Endocrinology, 2022)
Osteoporosis and osteoarthritis are common diseases in an aging society, are considered metabolic diseases, and affect the quality of life of older adults. In addition, the gut microbiome is considered an additional organ to regulate bone metabolism. In the past decade, people have been studying the relationship between gut microbiota and bone metabolism. The role and mechanism of the gut microbiota in regulating bone metabolism is very important to improve the development of osteoporosis and osteoarthritis. Depletion of the gut microbiota as a method of studying the role of the gut microbiota was provided strategies to enhance the role of the gut microbiota in regulating osteoporosis and osteoarthritis. In this review, we discuss how depletion of the gut microbiota affects osteoporosis and osteoarthritis.